Does the FSH/LH ratio in the serum on the third day of the cycle predict ICSI success? - (:unkn) unknown (My University, 2012)
Amaç: Siklusun 3.günü normal FSH değeri olan kadınlarda follikül stimule edici hormon (FSH)/luteinize edici hormon (LH) oranının sitoplazma içi sperm enjeksiyonu (ICSI) başarısının öngörülebilirliğini araştırmak. Hastalar ve Yöntem: Uzun protokol ve rekombinant folikül stimüle edici hormon kullanılarak ICSI tedavisi alan ardışık yüz doksan dokuz infertil kadın retrospektif olarak analiz edildi. Grup A, B, C ve D sırasıyla FSH/LH oranları <1; ≥1 ile <1.5 arası; ≥1.5 ile ≤2 arası ve >2 olan kadınlardan oluşturuldu. Transfer başına klinik gebelik ve implantasyon oranları karşılaştırıldı. Bulgular: Transfer başına klinik gebelik ve implantasyon oranları gruplar arasında benzer idi. Sonuç: Siklusun 3.günü FSH/LH oranı ICSI sikluslarında tedavi sonuçlarını normal 3. gün FSH seviyesi olan kadınlarda öngöremez.

Objective: To determine whether the follicule stimulating hormone (FSH)/ luteinizing hormone (LH) ratios on the third day of the cycle predict intracytoplasmic sperm injection (ICSI) outcomes in women with normal day 3 FSH levels. Patients and Methods: A retrospective cohort analysis of one hundred and ninety-nine consecutive women undergoing ICSI treatment with long-down regulation and recombinant follicular stimulating hormone injections was carried out in a University hospital. Four groups were compared in terms of in vitro fertilization (IVF) outcomes. Groups A, B, C and D consisted of women with FSH/LH ratios of <1; ≥1 and <1.5; ≥1.5 and ≤2 and >2, respectively. The clinical pregnancy and implantation rates per transfer were compared. Results: There was no significant difference between the groups regarding the clinical pregnancy or implantation rates per transfer. Conclusion: It appears that the basal FSH/LH ratio does not predict the cycle outcome in ICSI cycles in women with normal day 3 FSH levels.
Siklusun 3.günü normal FSH değeri olan kadınlarda FSH/LH oranı ICSI başarısını öngörebilir mi?
Keywords: Genel ve Dahili Tıp